Pengaruh strategi kepemimpinan terhadap keberhasilan transformasi bank syariah - Rohmah, Sabana Nur (Maliki Interdisciplinary Journal, 2025)
The transformation of Islamic banking in Indonesia is a strategic phenomenon that demands adaptive and innovative capabilities from leaders. This study aims to analyze the influence of leadership strategies on the success of Islamic banking transformation by examining the relationship between transformational leadership style, work motivation, organizational culture, and digital transformation implementation. A descriptive qualitative approach was used, synthesizing various previous research findings. A study by Muchran & Muchriady (2017) found that transfor mational leadership style can increase work motivation, although its direct impact on performance is insignificant without the support of a strong motivational system. Rianto (2021) demonstrated that transformational leadership is a key variable in strategic change and the formation of learning organizations in Islamic banks in DKI Jakarta. Elfrida et al. (2024) emphasized that leadership is a top priority for the successful implementation of a bank’s digital transformation. Furthermore, Siswanto (2014) and Azzam & Wardana (2022) demonstrated that leadership based on Islamic spiritual and cultural values ​​increases employee commitment and performance. Based on this synthesis, an adaptive, visionary, and Islamic-based transformational leadership strategy has proven to be a key driver of the success of Islamic banking organizational transformation. The success of the transformation is not only